Local Infection is the Most Common Complication after the Using of Modified Tension-Band Wiring in the Treatment of Close Patellar Fractures - Ghareeb Ullah, Samreen Asghar, Irshad Ahmed, Habibullah, Ishtiaque Ali Langah, Jamshed Khan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: Patellar fracture is about one percent of all the skeletal fracture. It is problematic due tothe loss of extensor mechanism of the knee joint, loss of articular congruity and stiffness of the kneejoint. Now a days MTBW Modified tension band wiring is the best procedure for patellar fracture due to the dramatic decrease